The Rise of De Facto State’s Foreign Policy Identity: From Self-Proclamation to International Legal Subjectivity. The Case of Abkhazia - A. V. Pavlova (Международная аналитика, 2024)
The article focuses on the foreign policy identity of the de facto state, citing Abkhazia, which gained partial recognition from Russia and a number of other states, as an example. Using comparative analysis of the Abkhazian Intellectuals’ Adresses (1977 and 1988) and content analysis of the annual Presidential Addresses as basic research methods, the study attempts to answer the question: what is the foreign policy identity of the de facto state (from 2008 – partially recognized state) under issue. The conducted research concludes that the conceptual foundations of Abkhazian foreign policy identity, formulated in the Intellectuals’ Addresses, are reflected in the oﬃcial discourse and reproduced at the level of everyday perception, still they are not static. The main implication to be made is that although today Abkhazia is increasingly positioned as a sovereign state, the opposite – Abkhazia’s identity as a de facto state – is still evident enough in oﬃcial speeches and everyday communication.